2017
DOI: 10.1057/s41271-017-0098-4
|View full text |Cite
|
Sign up to set email alerts
|

Workplace violence among female sex workers who use drugs in Vancouver, Canada: does client-targeted policing increase safety?

Abstract: Workplace violence, by clients or predators, poses serious negative health consequences for sex workers. In 2013, the Vancouver (British Columbia), Canada Police Department changed their guidelines with the goal of increasing safety for sex workers by focusing law enforcement on clients and third parties, but not sex workers. We sought to examine the trends and correlates of workplace violence among female sex workers (FSW) before and after the guideline change, using data collected from prospective cohorts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
1
11
0
2
Order By: Relevance
“…Aligning with findings from other studies, this suggests that partial legalization, such as the removal of only some aspects of criminal laws and regulation of sex workers is necessary, but not sufficient for reducing sexual violence as a risk factor for HIV 52 . This is consistent with previous modeling and empirical work, suggesting that only through full decriminalization, such as full removal of laws targeting sex industry; access to safer work environments; and prevention of violence and harassment by police could law reform as a structural determinant avert violence and HIV infections 10,51 . Finally, empirical research pre and post law reform has shown that in settings where clients and third parties are criminalized but not sex workers, rates of both sexual violence was unchanged from full criminalization 53 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Aligning with findings from other studies, this suggests that partial legalization, such as the removal of only some aspects of criminal laws and regulation of sex workers is necessary, but not sufficient for reducing sexual violence as a risk factor for HIV 52 . This is consistent with previous modeling and empirical work, suggesting that only through full decriminalization, such as full removal of laws targeting sex industry; access to safer work environments; and prevention of violence and harassment by police could law reform as a structural determinant avert violence and HIV infections 10,51 . Finally, empirical research pre and post law reform has shown that in settings where clients and third parties are criminalized but not sex workers, rates of both sexual violence was unchanged from full criminalization 53 .…”
Section: Discussionsupporting
confidence: 90%
“…Increased legal restrictions on sex work has been shown to move activities to more hidden settings to avoid detection by uniformed officers, alongside increased vulnerability to violence and HIVrisk behaviors such as unprotected sex 50 . Even when enforcement efforts prioritize clients or third parties, violence affecting sex workers persists 51 . In contrast, the degree of the relationship between sexual violence and HIV does not vary across legal contexts.…”
Section: Discussionmentioning
confidence: 99%
“…No quantitative studies examined the effects of the criminalisation of sex purchase in isolation, or the effects of decriminalisation. Outcomes reported included the following: sexual or physical violence ( n = 10) [5759,6369], HIV and/or STI prevalence ( n = 15) [54,60,63,67,7078], condom use ( n = 5) [71,74,7882], access to services ( n = 8) [56,61,63,71,80,8385], aspects of drug use ( n = 6) [27,46,62,63,66,86,87], and emotional ill health ( n = 3) [55,60,88]. Two studies focused on the association between criminalisation and social and criminal justice factors including further extortion by the police or history of arrest [63], any contact with the criminal justice system, being a migrant, and unstable housing [60].…”
Section: Resultsmentioning
confidence: 99%
“…We synthesised 4 studies that reported an effect estimate associated with a mandatory registration separately [79,81,89,90] but considered lawful and unlawful repressive police activities within the regulatory system as part of the pooled analysis [63,72,91]. Three studies presented effect estimates associated with a policy change, STIs, and rushing negotiation with clients, and were also considered separately [57,77,92]. Twenty studies reported on outcomes relating to HIV/STI prevalence, violence, and condom use, on which our primary meta-analyses are based.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the accessibility of alcohol and illicit drugs in EDCs potentiates the risks vulnerable FED experience in these spaces. Qualitative and quantitative evidence generated in Baltimore (Sherman, Reuben, Chapman, & Lilleston, 2011), Sherman et al, 2011aSherman et al, , 2017 Detroit (Draus, Roddy, & Asabigi, 2015;Knittel, Graham, Peterson, Lopez, & Snow, 2019), Vancouver (Argento, Chettiar, Nguyen, Montaner, & Shannon, 2015;Duff et al, 2017;Prangnell et al, 2018;Puri, Shannon, Nguyen, & Goldenberg, 2017), and Cambodia (Draughon Moret et al, 2016;Maher et al, 2011) suggests urban FED and other women involved in indoor sex industries use substances as mechanisms for coping with stressful and sexually coercive work environments, particularly in venues characterized by high drug availability and prevalent use among staff and dancers. FED may also use specific substances, like cocaine or other stimulants, to heighten awareness/vigilance in unsafe settings or situations (e.g.…”
Section: Introductionmentioning
confidence: 99%